Deteksi Dini Faktor Risiko Penyakit Tidak Menular melalui Pemeriksaan Gula Darah dan Kolesterol Serta Edukasi Pola Hidup Sehat pada Masyarakat di Kelurahan Kampung Bandar - Arnila Melina; Muhammad Ridho; Meilanny Rahmatillah; Vina Rizki Adinda Salsabila; Shafira Salsabila Nizar; Ananda Asha Rizki; Dwi Damayanti; Alfina Damayanti; Newi Syahputri Purba; Shalsabila Putri Hanafiah; Yuwinda Ratna Dewi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Non-Communicable Diseases (NCDs) such as diabetes mellitus and dyslipidemia have become a major public health challenge. The increasing prevalence of NCDs is largely influenced by unhealthy lifestyles, including high consumption of fatty and sugary foods, lack of physical activity, and low awareness of routine health check-ups. Early detection and health education play a crucial role in preventing NCD-related complications. This study aims to identify blood glucose and cholesterol levels among the community in Kampung Bandar Village and provide health education on healthy lifestyles. A descriptive quantitative method was applied to 50 respondents using random blood glucose and total cholesterol examinations. The results showed that the majority of respondents were categorized as prediabetes to diabetes for blood glucose levels, and borderline high to high for cholesterol levels. The health education emphasized the importance of balanced diet, regular exercise, and periodic health check-ups. This activity is expected to increase community awareness of the importance of early detection and lifestyle modification in preventing NCDs.